Implant Placement in Site of Plexiform Ameloblastoma After Dredging. A Clinical Report - Regmi, S.; Joshi, S. P.; Shrestha, P.; Sah, S. K.; Verma, A.; Karna, G. (Journal of Nepalese Prosthodontic Society, 2021)
Ameloblastoma is a benign but aggressive neoplasm of odontogenic origin with a predilection of the mandible. It can be of various types based on histopathological features. Follicular and plexiform ameloblastoma are the most common types of ameloblastoma. There are various methods for management of ameloblastoma amongst which dredging is considered a conservative surgical procedure which involves enucleation or deflation and enucleation and repeated removal of scar tissues to accelerate new bone formation. Placement of implant at the site of newly regenerated bone after dredging is completed with repeated examination of tumour mass histopathology. This report documents the placement of implant in newly formed mature bone after successful dredging of plexiform ameloblastoma